Early life stages of Calanus pacificus are neither exposed nor sensitive to low pH waters. (15th November 2019) - McLaskey, Anna K; McElhany, Paul; Busch, D Shallin; Maher, Michael; Winans, Amanda K; Keister, Julie E
Abstract: We characterized the vertical distribution of Calanus pacificus eggs and larvae and the carbonate chemistry that they are exposed to in Puget Sound, WA. We found that, under stratified conditions, more than 90% of eggs and nauplii stages 1–4 were distributed above the pycnocline, in seawater with pH higher than 7.7. In addition, eggs and larvae from 101 females were reared for 5 days under a range of pH conditions (7.2–8.0) to investigate how pH sensitivity varies among individuals. We observed a slight increase in naupliar survival at pH 7.3 in Individual Brood experiments, while in Mixed Brood experiments, exposure to pH 7.3 led to a small decline in hatching success. In a Split Brood experiment, inter-individual variability among different females' broods masked pH effects. These results indicate that C. pacificus early life stages are generally tolerant to short-term direct effects of ocean acidification.